Gestational weight gain and fetal growth in underweight women. Issue 1 (December 2016) - Zanardo, Vincenzo; Mazza, Alessandro; Parotto, Matteo; Scambia, Giovanni; Straface, Gianluca
Abstract Background Despite the current obesity epidemic, maternal underweight remains a common occurrence with potential adverse perinatal outcomes. Methods We aimed to investigate the relationship between weight gain during pregnancy, and fetal growth in underweight women with low and late fertility. Women body mass index (BMI), defined according to the World Health Organization's definition, gestational weight gain (GWG), defined by the Institute of Medicine and National Research Council and neonatal birth weight were prospectively collected at maternity ward of Policlinico Abano Terme (Italy) in 793 consecutive at term, uncomplicated deliveries. Results Among those, 96 (12.1 %) were categorized as underweight (BMI < 18.5 kg/m2 ), 551 (69.5 %) as normal weight, 107 (13.4 %) as overweight, and 39 (4.9 %) as obese, respectively. In all mother groups, GWG was within the range recommended by IOM 2009 guidelines. However, underweight women gained more weight in pregnancy (12.8 ± 3.9 kg) in comparison to normal weight (12.3 ± 6.7 kg) and overweight (11.0 ± 4.7 kg) women and their GWG was significantly higher (p  < 0.001) with respect to obese women 5.8 ± 6.1 kg). In addition, offspring of underweight women were comparable in size at birth to offspring of normal weight women, whereas they were significantly lighter to offspring of both overweight and obese women. Conclusions Pre-pregnancy underweight does not impact birth weight of healthy, term neonates in presence of normal GWG. Presumably, medical or personal efforts to reach 'optimal' GWG could be a leading choice for many women living in industrialized and in low-income countries.